2012
DOI: 10.1007/s00120-012-3033-0
|View full text |Cite
|
Sign up to set email alerts
|

Phytotherapie bei benignem Prostatasyndrom und Prostatakarzinom

Abstract: In some countries plant extracts have belonged to the most popular drugs for the treatment of the benign prostatic syndrome (BPS) for decades; however, only few of the large number of published studies meet the criteria of the WHO benign prostatic hyperplasia (BPH) consensus conference. The few placebo-controlled long-term (study period >6 months) studies suggest a positive effect of some extracts (saw palmetto fruit, β-sitosterol, urtica, rye grass and a saw palmetto/urtica combination) on lower urinary tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…The results showed that β-sitosterol inhibits 5α-R2 at a very high concentration (2.7 mM), but decreases the weight of the prostate in gonadectomized hamsters treated with T. Thus, the pharmacological effect produced by β-sitosterol is a consequence of its binding to the AR [82]. …”
Section: Recent Advances In New Steroidal and Non-steroidal Inhibitormentioning
confidence: 99%
“…The results showed that β-sitosterol inhibits 5α-R2 at a very high concentration (2.7 mM), but decreases the weight of the prostate in gonadectomized hamsters treated with T. Thus, the pharmacological effect produced by β-sitosterol is a consequence of its binding to the AR [82]. …”
Section: Recent Advances In New Steroidal and Non-steroidal Inhibitormentioning
confidence: 99%
“…Als häufigste Gründe für die Behandlung mit pflanzlichen Arzneimitteln werden eine gute Verträglichkeit und eine daraus resultierende gute Compliance der Patienten beschrieben. Daher erfolgt häufig die Erstbehandlung mit Phytopharmaka [3].…”
unclassified